2019
DOI: 10.3390/toxins12010009
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Clostridial Neurotoxin Produced by Strain IBCA10-7060 Is Immunologically Equivalent to BoNT/HA

Abstract: Background: Botulinum neurotoxins (BoNTs) comprise seven agreed-on serotypes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Botulinum toxin (BoNT), the most potent toxin known to humans, (1,2) is produced by the obligate anaerobic organism Clostridium botulinum with 7 neurotoxin serotypes identified to date (A-G). (3,4) Mechanisms of BoNT intoxication include ingestion of food contaminated by preformed toxin, infection of wounds, (5) toxicoinfection in infants and adults, iatrogenic chemodenervation. (6) An additional theoretical mechanism is dispersal of a weaponized toxin (7,8) After toxicoinfection in infants, foodborne intoxication is most common; there is also a rising incidence of wound botulism among intravenous drug users.…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum toxin (BoNT), the most potent toxin known to humans, (1,2) is produced by the obligate anaerobic organism Clostridium botulinum with 7 neurotoxin serotypes identified to date (A-G). (3,4) Mechanisms of BoNT intoxication include ingestion of food contaminated by preformed toxin, infection of wounds, (5) toxicoinfection in infants and adults, iatrogenic chemodenervation. (6) An additional theoretical mechanism is dispersal of a weaponized toxin (7,8) After toxicoinfection in infants, foodborne intoxication is most common; there is also a rising incidence of wound botulism among intravenous drug users.…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum neurotoxin (BoNT) is one of the most toxic substances known in nature and classified as a Tier 1 select agent by the Centers for Disease Control and Prevention (CDC) in the United States [ 1 , 2 , 3 ]. There are at least seven immunologically distinct serotypes of BoNT (A–G) that include more than 40 subtypes [ 4 , 5 , 6 , 7 , 8 ]. BoNT/E is one of the four BoNT serotypes (with BoNT/A, BoNT/B, and rarely BoNT/F) known to cause human botulism.…”
Section: Introductionmentioning
confidence: 99%
“…One of the initial variants of BoNT identified through in silico data mining of gene sequences was BoNT/H. This was identified from a toxin reported to cause infant botulism in 2014 by the C. botulinum strain IBCA10-7060 [ 53 ]. Initially, the authors presumed that it was a novel variant, a bivalent strain of B2 toxin, which was denoted as serotype H. In early experiments, it was found that the toxin could be weakly neutralised by antibodies against currently known serotypes.…”
Section: Recombinant Botulinum Toxin and Application Of In Silico mentioning
confidence: 99%